The Production of Food and Fiber: An Adaptation of CoP Features for Sustainable Water Use in Agribusiness - Harris, Keith D.; James, H. S. (My University, 2017)
Fresh water and arable land are essential for agricultural production and food processing. However, managing conflicting demands over water and land can be challenging for business leaders, environmentalists and other stakeholders. This paper characterizes these challenges as wicked problems. Wicked problems are ill-formed, fuzzy, and messy, because they involve many clients and decisions makers with conflicting values. They are also not solvable, but rather must be managed. How can agribusiness leaders effectively manage wicked problems, especially if they have little practice in doing so? This paper argues that a Community of Practice (CoP) and its tripartite elements of domain, community and practice can be effective in helping businesses manage wicked problems by focusing on the positive links between environmental stewardship and economic performance. Empirically, the paper examines three agribusinesses to assess the extent in which CoP is used as a strategy for sustainable water management.
Citation: Harris, K. D., & James, H. S. (2016). The Production of Food and Fiber: An Adaptation of CoP Features for Sustainable Water Use in Agribusiness. Sustainability, 8(11), 15. doi:10.3390/su8111189
Keywords: Agribusiness; Community Of Practice; Environmentalism; Knowledge; Relationships; Wicked Problems